Effect of Trichloroethylene on the Competitive Behavior of Toluene-Degrading Bacteria - Mars, Astrid E. (American Society for Microbiology, 1998)
The influence of trichloroethylene (TCE) on a mixed culture of four different toluene-degrading bacterial strains (Pseudomonas putida mt-2, P. putida F1, P. putida GJ31, and Burkholderia cepacia G4) was studied with a fed-batch culture. The strains were competing for toluene, which was added at a very low rate (31 nmol mg of cells [dry weight](−1) h(−1)). All four strains were maintained in the mixed culture at comparable numbers when TCE was absent. After the start of the addition of TCE, the viabilities of B. cepacia G4 and P. putida F1 and GJ31 decreased 50- to 1,000-fold in 1 month. These bacteria can degrade TCE, although at considerably different rates. P. putida mt-2, which did not degrade TCE, became the dominant organism. Kinetic analysis showed that the presence of TCE caused up to a ninefold reduction in the affinity for toluene of the three disappearing strains, indicating that inhibition of toluene degradation by TCE occurred. While P. putida mt-2 took over the culture, mutants of this strain which could no longer grow on p-xylene arose. Most of them had less or no meta-cleavage activity and were able to grow on toluene with a higher growth rate. The results indicate that cometabolic degradation of TCE has a negative effect on the maintenance and competitive behavior of toluene-utilizing organisms that transform TCE.